DESCRIPTION STUDY OF PANDEGLANG COMMUNITY KNOWLEDGE ON NATURAL DISASTERS AND GOVERNMENT POLICIES RELATED TO NATURAL DISASTER PREPAREDNESS IN 2022 - Ginting, Novi Anggraini; Adisasmito, Wiku Bakti Bawono (UI Scholars Hub, 2022)
Pandeglang Regency, which is a disaster-prone area, requires people who have sufficient knowledge to create community preparedness in dealing with disasters and can assist in the disaster mitigation process. This study aims to find out how the community's knowledge and community preparedness related to natural disasters and what efforts have been made by the government to improve the readiness of the people of Pandeglang Regency. This research method is descriptive and quantitative with 451 respondents. The results of the study showed that the people of Pandeglang Regency still did not know correctly the different types of threats or types of disasters that occurred, 59% of respondents were on standby to prepare their emergency items, but there were still many people who did not keep essential telephone numbers needed in an emergency, the community Pandeglang Regency prefers information sources through electronic media, this is supported by the demographic factor of the Pandeglang Regency population, the majority of which are aged 30 to 49 years or generation X, who are still not familiar with the development of internet technology.